IMPLEMENTATION OF RELIGIOUS MODERATION PRACTICES IN MINORITY ISLAMIC VILLAGES IN SEA VILLAGE, PINELENG DISTRICT, MINAHASA REGENCY - Fitri Mamonto; Musafar Musafar; Hadirman Hadirman (Peminat Ilmu Ushuluddin, 2022)
This article is a study related to religious moderation in minority Islamic villages. Moderation of religion in the Muslim-Christian community in Sea Village, Pineleng District is going very well in social interactions and activities. This study raises the issue of how the practice of religious moderation in socio-religious life in a minority Islamic village in Sea Village. The purpose of this study is to describe the practice of religious moderation in socio-religious life in a minority Islamic village in Sea Village. The method used in this research is descriptive-qualitative with a phenomenological approach. The results showed that the practice of religious moderation in the socio-religious life of the Muslim community in Sea Village was applied in social activities, religious activities, and political activities and “village” leadership. The implication of this research is as an effort to maintain cohesiveness and increase religious moderation that has been implemented and maintain it continuously from generation to generation to become a miniature of religious moderation in North Sulawesi.